Yam (Dioscorea ssp.) domestication by the Nago and Fon ethnic groups in Benin - Mignouna, Hodeba D.; Dansi, A. (Springer, 2003)
Guinea yams (Dioscorea cayenensis-rotundata complex; D. rotundata Poir. and D. cayenensis Lam.) have been described as resulting from a process of domestication of wild yams of the section Enantiophyllum by African farmers. Although currently practised by few farmers, the process of yam domestication is still on-going in Benin. In order to document the practices used and the indigenous knowledge maintained by Nago and Fon farmers, 27 villages were surveyed. In total, 57 farmers domesticating yam were identified, and 68 yams newly domesticated (or in domestication) were collected. Fon and Nago farmers domesticate yam mainly to widen the genetic basis of the existing diversity or for simple curiosity. Among the three wild yams species (D. abyssinica Hochst. ex Kunth, D. praehensilis Benth. and D. burkilliana J. Miège) used, D. praehensilis is the most important and the most exploited. Tuber of the wild yams are collected either in the bush (most often near the village) or in the forests (far from the village) during hunting. The domestication process consists of bringing into cultivation selected individuals which go through intense vegetative multiplication and selection procedures (over a lengthy but variable period of time) that induce morphological and biochemical changes in the plant mainly at the tuber level. Individuals resulting from these manipulations were found to be, either similar or identical to known landraces or completely new based on both morphological and isozyme analysis. Because it leads to some new cultivars, this process of domestication has potential in yam breeding and appears to be a strategy that could be useful to breeders, while developing a methodology for participatory breeding of yam.